Development of an advanced nano-satellite VELOX-I – attitude control system - Ng, Yu Lian. (2013)
The VELOX series of satellite was started in Nanyang Technological University as an initiative to train its undergraduate students in space technology. The first satellite in the VELOX series is called VELOX-I. VELOX-I is a nano-class satellite weighing approximately 5kg and comes equipped with a camera for earth imaging operations. The attitude of a satellite refers to its orientation in space. Attitude control refers to the use of onboard actuators to maneuver the satellite to a desired attitude such as pointing the camera towards Earth or facing the solar panels towards the sun for power harvesting. The attitude control system (ACS) is responsible for performing the attitude control operations onboard the satellite. The primary actuators used for attitude control onboard VELOX-I are reaction wheels which operates on the principle of conservation of momentum. The moment of inertia of the satellite describes the relationship between the changes in the satellite rotation speed due to an applied torque. As such, an accurate moment of inertia value would benefit the attitude controller design. Experiments have conducted to measure the moment of inertia of an air bearing table test setup. In the experiments, the environmental frictional torque was characterized as well. The frictional torque is found to be linear and can be approximated to be 88.75% of the commanded torque to the actuators.